FAKTOR – FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS KERJA KARYAWAN PT. TEKNIK VISUAL GRAPHIA PONTIANAK - Adhitya Kurniawan; Achmadi Achmadi; Okianna Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstrackThis study aims to determine whether the level of education, incentives, age and work experience affect the work productivity of employees at PT. Pontianak Visual Graphia Techniques. The research method used is descriptive research in the form of qualitative research. The data sources of this study used data from interviews and observations, consisting of 3 respondents as admins and 1 respondent as supervisor. To test the validity of the research data, triangulation of sources and theories was carried out. Based on the tests conducted, the results of this study indicate that the level of education, incentives, age and work experience significantly affect the work productivity of PT. The Pontianak Visual Graphia Technique as for other factors that are considered to have an effect on work productivity include attitudes, work ethics, discipline and how the relationship between employees and employees and leaders.Keywords: Education level, incentives, age, work experience, human resources